Wedge defect: etiology, clinical features, classification and modern treatment approaches (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
A wedge defect (abfraction or non-carious cervical lesion, NCCL) is a defect in the cervical (neck) zone of the teeth that is not associated with caries of the enamel and dentin layers, resulting from mechanical and chemical exposure. This article is based on the etiopathogenesis of the wedge defect, morphological types, stages of development and phases of rejection (Yakovleva V.A A wedge defect A wedge defect (abA wedge defecfwedge defect (abfraction or non-carious cervical lesion, NCCL) is a defect in the cervical (neck) zone of the teeth that is not associated with caries of the enamel and dentin layers, resulting from mechanical and/or chemical exposure. This article is based on the etiopathogenesis of the wedge defect, morphological types, stages of development and phases of rejection (Yakovleva V.I., Prosveryak G.P., Makhmudkhanov S.M., Fyodorov F.A., Drozhina V.A. based on their classifications), diagnostic capabilities (clinic, radiology, optical-and laboratory methods), as well as the results of international and domestic experiments (finite element analysis, retrospective clinical observations, prospective restorative studies) are analyzed. Based on their classifications), diagnostic capabilities (clinic, radiology, optical-and laboratory methods), as well as the results of international and domestic experiments (finite element analysis, retrospective clinical observations, prospective restorative studies) are analyzed. In the treatment strategy, it was shown that the compatibility of etiological (occlusive stress and parafunction), conservative (remineralization, desensitization) and restorative (adaptive restorations, bioactive materials, orthopedic approaches) components is necessary. The article proposes a diagnostic-therapeutic algorithm for clinical practice and directions for future research.